Economic analysis : theory and application - Ferguson, C. E.; Maurice, S. Charles (Homewood, Ill. : R. D. Irwin, 1978)
The textbook is designed for undergraduate courses in basic micro-economics - the theory of value and distribution. This third edition has two major objectives. The primary purpose is to present the basic fundamentals of price theory. The secondary, but quite important, purpose is to illustrate how the fundamentals of price theory can be applied to the solution of real-world, decision-making problems and to give students experience in solving these problems.
Includes bibliographical references and index.
rpm 28/08/2017
Loans
Keywords: Economics